Food Science in Developing Countries : A Selection of Unsolved Problems - National Academy of Sciences - National Research Council, Washington, DC.; National Academy of Sciences - National Research Council, Washington, DC. (Washington : Distributed by ERIC Clearinghouse, 1974)
Presented are summaries of 42 unsolved problems in food science which exist in various developing countries throughout the world. Problems deal with new foods, food processing, food composition, nutrition, and health. Each problem presented includes the problem description, background information, possible approaches to solutions, special requirements, a bibliography, and key contacts for further information relating to the problem. (SL)
Microfiche.
Keywords: Agriculture; Developing Nations; Food; Foreign Countries; Health; Nutrition; Research Needs; Research Opportunities; Research Problems; World Problems; Reports, Research